Assessment of ecological plasticity and stability of sunflower hybrids (Helianthus annuus l.) in Ukrainian Steppe - Yeremenko, O. A.; Kalytka, Valentyna; Kalenska, S. M.; Malkina, V. M. (My University, 2018)
Modern hybrids of sunflower show a pronounced response to changes in agrometeorological conditions of their growing. The research was carried out during 2013-2015 under conditions of insufficient moisture in the Southern steppe of Ukraine. Field and mathematical-statistical methods were used.
Keywords: sunflower; agrometeorological conditions; adaptability; stable yield; mathematical-statistical methods